Thematic Progression in Song Lyrics: Comparison of English Songs Lyrics Written by Indonesian and English Songwriters - Nindya Fraya Maharani Pagih (Passage, 2017)
The present study investigates the appearance of Thematic Progression and Lexicogrammatical Features in English song lyrics written by English and Indonesian songwriters by applying theories of Systemic Functional Grammar by using Hallidays Lexicogrammatical Features and Danes’ Thematic Progression framework. This study discovers that the thematic Progression patterns and Lexicogrammatical features found in the data are similar. This study revealed that in English song lyrics written by both Indonesian and English songwriters, the appearance of the most frequent Thematic Progression patterns and lexicogrammatical Features are similar. The data showed that Multiple Theme Progression appears as the most frequent Thematic Progression pattern. The data also showed the use of Personal Pronoun appears as the most frequent Lexicogrammatical feature. These findings suggested that the texts are coherent and, by the dominant use of personal pronoun ‘I’ and ‘you’, the songwriters tend to speak directly to their listeners so it could be easily understood by the readers/listeners. Keywords: Theme, Thematic Progression, Lexicogrammatical Features, song lyrics